B Cell Depletion Inhibits Fibrosis via Suppression of Profibrotic Macrophage Differentiation in a Mouse Model of Systemic Sclerosis. Issue 11 (28th September 2021) - Numajiri, Hiroko; Kuzumi, Ai; Fukasawa, Takemichi; Ebata, Satoshi; Yoshizaki‐Ogawa, Asako; Asano, Yoshihide; Kazoe, Yutaka; Mawatari, Kazuma; Kitamori, Takehiko; Yoshizaki, Ayumi; Sato, Shinichi
Abstract : Objective: We undertook this study to investigate the effect of B cell depletion on fibrosis in systemic sclerosis (SSc) and its mechanism of action. Methods: Mice with bleomycin‐induced SSc (BLM‐SSc) were treated with anti‐CD20 antibody, and skin and lung fibrosis were histopathologically evaluated. T cells and macrophages were cocultured with B cells, and the effect of B cells on their differentiation was assessed by flow cytometry. We also cocultured B cells and monocytes from SSc patients and analyzed the correlation between fibrosis and profibrotic macrophage induction by B cells. Results: B cell depletion inhibited fibrosis in mice with BLM‐SSc. B cells from mice with BLM‐SSc increased proinflammatory cytokine–producing T cells in coculture. In mice with BLM‐SSc, B cell depletion before BLM treatment (pre‐depletion) inhibited fibrosis more strongly than B cell depletion after BLM treatment (post‐depletion) ( P < 0.01). However, the frequencies of proinflammatory T cells were lower in the post‐depletion group than in the pre‐depletion group. This discrepancy suggests that the effect of B cell depletion on fibrosis cannot be explained by its effect on T cell differentiation. On the other hand, profibrotic macrophages were markedly decreased in the pre‐depletion group compared to the post‐depletion group ( P < 0.05). Furthermore, B cells from mice with BLM‐SSc increased profibrotic macrophage differentiation in coculture ( P < 0.05). In SSc patients, the extent of profibrotic macrophage induction by B cells correlated with the severity of fibrosis ( P < 0.0005). Conclusion: These findings suggest that B cell depletion inhibits tissue fibrosis via suppression of profibrotic macrophage differentiation in mice with BLM‐SSc, providing a new rationale for B cell depletion therapy in SSc.